Synthesis and Insilico Approaches of Ethyl 1-Benzenesulfonyl -2-[(E)-2- (2 Methylphenyl) Ethenyl] Indole -3-Carboxylate with Human Renin Complexed with Inhibitor - Ramathilagam, C. (Pharmaceutical Science: New Insights and Developments Vol. 2, 2025)
The present study aims to create a new type of renin inhibitor. The renin protein was therefore chosen as the target. Advanced computational research is carried out in the field of drug discovery in In silico. To cut down on the expense and duration of drug discovery, screening techniques are often and widely employed. Currently, hypertension is associated with kidney diseases, in which excess fluid in the kidney damages the walls and exerts pressure resulting in End-stage renal disease (ESRD). Various proteins play important roles in hypertension and a number of drugs have been tested for their efficacy in modulating hypertension. Renin is an aspartyl protease involved in the production of angiotensin II, a potent vasoconstrictor. Renin-inhibitors have the potential to be helpful in the treatment of hypertension since they can prevent blood vessel constriction. This justification leads to the synthesis of novel indole compounds and their antihypertensive efficacy being assessed. Docking studies using Molegro Virtual Docker (MVD) on the human Renin complexed with inhibitor (PDB ID:2IKO) show their role in the antihypertensive activity of the molecule and explain the higher potency of the compound based on ReRanking scores and binding poses of the molecule.